Sodium ion-proton antiport in a marine bacterium. - Niven, D F (1978)
Alteromonas haloplanktis ejected protons in response to a brief respiratory pulse; the rate of decay of the resulting pH change was accelerated when Na+ was present in the suspension medium. The addition of an anaerobic NaCl solution to an essentially Na+-free anaerobic bacterial suspension induced the acidification of the suspension medium. These results and others discussed provide substantial evidence for the existence of an Na+-H+ antiporter in this organism.